2009
DOI: 10.1152/ajpgi.00050.2009
|View full text |Cite
|
Sign up to set email alerts
|

EnterohemorrhagicEscherichia colisuppresses inflammatory response to cytokines and its own toxin

Abstract: Infection with the enteric pathogen enterohemorrhagic Escherichia coli (EHEC) causes a variety of symptoms ranging from nonbloody diarrhea to more severe sequelae including hemorrhagic colitis, altered sensorium and seizures, and even life-threatening complications, such as hemolytic uremic syndrome and thrombotic thrombocytopenic purpura. The more severe consequences of EHEC infection are attributable to the production of Shiga toxin (Stx) and its subsequent effects on the vasculature, which expresses high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
4
24
1
Order By: Relevance
“…Our results indicated that E. coli O157:H7 attenuated both basal and TNF-␣-induced activation of NF-B p65 signaling in HT-29 cells 3 h postinfection. In contrast to our results, a previous study indicated that EHEC infection enhanced NF-B signaling in T84 cells (24). IL-18 is an important inflammatory cytokine involved in both innate and adaptive immunity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results indicated that E. coli O157:H7 attenuated both basal and TNF-␣-induced activation of NF-B p65 signaling in HT-29 cells 3 h postinfection. In contrast to our results, a previous study indicated that EHEC infection enhanced NF-B signaling in T84 cells (24). IL-18 is an important inflammatory cytokine involved in both innate and adaptive immunity.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with previous studies showing that E. coli O157:H7 infection elevated IL-8 mRNA expression in T84 cells (24,39) and Caco-2 cells (40). In addition, Bellmeyer et al (24) reported that EHEC infection reduced IL-8 production in HT-29 cells in response to TNF-␣ challenge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results support data obtained on rabbit enterocytes (6) and human epithelial cell lines cells (9)(10)(11), which showed a type III secretion dependent reduction of IL-8 production. Similar results were recently reported for EHEC, which can downregulate the proinflammatory cytokine production by intestinal epithelial cells in response to its own Shiga toxin (20) and uses the effector NleH1 to subvert NF-kB-dependent transcription by binding to the ribosomal protein s3 (21).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, recent evidence suggests that a number of A/E pathogens, in turn, generate factors that down-regulate the inflammatory response thereby preserving the integrity of epithelial cells that is critical for colonization. 41 These data emphasize the importance of immune-mediated regulation of bacterial and host cell interactions.…”
Section: Stats and Adaptive Immunity (Fig 2)mentioning
confidence: 93%